Praktik Pembulatan Timbangan Pada Jasa Usaha Laundry Perspektif Hukum Ekonomi Syariah (Studi Kasus Di Desa Candimulyo Kecamatan Dolopo Kabupaten Madiun) - Laili, Annisa Nur; Kadenun, Kadenun (Journal of Sharia Economic Law, 2024)
The background of this research is that rounding the scales is the process of rounding a scale on clothes that will be laundromated. At Bigi Berkah Laundry and Laundry Mbak Tutik, rounding the scales is done if the weight of the clothes does not meet the minimum amount that has been determined by the laundry business services then it will be rounded, to meet the requirements. Specified weight of clothing. Meanwhile, price rounding occurs when the initial price is smaller than the rupiah value, so it will be rounded to make it easier to provide returns. This thesis contains a problem formulation: (1) What is the practice of rounding scales and prices for the two laundry business services in Candimulyo Village, Dolopo District, Madiun Regency? (2) What is the practice of rounding off scales and prices for the two laundry business services in Candimulyo Village, Dolopo District, Madiun Regency from a Sharia Economic Law Perspective? This type of research was carried out qualitatively at the Candimulyo Village laundry businnes services, Dolopo District, Madiun Regency by collecting data through interview, observation, and documentation techniques. The conclusions are (1) Rounding off the scales for both laundry business services is carried out when the weight of the clothes does not meet the minimum limit that has been determined. Meanwhile, price rounding occurs when the initial price has a small rupiah denomination, so it will be rounded to make it easier to return it, (2) Judging from Sharia Economic Law regarding the practice of rounding scales and prices for both laundry business services is not permitted when costumers do not accept its application, this is because there is not specific argument that prohibits it, and this practice has become a urf (costum) that is accepted by society and its implementation can facilitate transactions.